2014
DOI: 10.1017/s1049096514001632
|View full text |Cite
|
Sign up to set email alerts
|

Race and the Tea Party in the Old Dominion: Split-Ticket Voting in the 2013 Virginia Elections

Abstract: In 2013, Virginia Republicans nominated two Tea Party conservatives for statewide offi ce: Ken Cuccinelli and Earl Walker Jackson, Sr. They diff ered in two signifi cant respects: (1) Cuccinelli has more political experience, and (2) Cuccinelli is white and Jackson is black. For this article, we used this quasi-experimental opportunity to examine the racial resentment explanation for Tea Party support. We found no evidence of voting patterns consistent with this characterization of Tea Party supporters. There … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…But now, similar to other recent studies (see Hood, Kidd, and Morris 2015;Hood and McKee 2015), it no longer appears that a candidate's race weighs as heavily in the voting calculus. Rather, in a period of highly polarized political parties, the most important litmus test seems to be ideological purity.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…But now, similar to other recent studies (see Hood, Kidd, and Morris 2015;Hood and McKee 2015), it no longer appears that a candidate's race weighs as heavily in the voting calculus. Rather, in a period of highly polarized political parties, the most important litmus test seems to be ideological purity.…”
Section: Resultssupporting
confidence: 80%
“…In effect, race is rendered irrelevant and instead ideology drives political behavior. On the flip side, another study found that in one particular analysis of vote choice, African-Americans were significantly less likely to vote for the black Republican Lieutenant Governor nominee E. W. Jackson in Virginia in 2013 (Hood, Kidd, and Morris 2015). But Jackson's abrasive demeanor sharply contrasts with the relatively softer styles displayed by Haley and Scott.…”
Section: Research On Minority Republicansmentioning
confidence: 99%
“…Others who conclude African American Republican candidates would help attract African American votes include Philpot (2007), Schildkraut (2013), Herron and Sekhon (2005), and Whitby (2007). Those who suggest Republicans would have little or nothing to gain by fielding African American Republican candidates include Fraga (2016); Kidd, Diggs, Farooq, and Murray (2007); Hood, Kidd, and Morris (2015); and Wehrkamp and Jeffries (2014). 4…”
Section: Race and Votingmentioning
confidence: 99%
“…After all, the institutions in question do have some of the same substantive implications; being linked on the ballot likely increases gubernatorial candidates’ interest in lieutenant-gubernatorial candidate characteristics, which may influence candidate-selection processes and outcomes. Indeed, recent work on lieutenant-governor candidates has focused on ticket splitting when the two offices run separately—especially in the context of descriptive representation of discriminated-against groups (Hood, Kidd and Morris 2015). Furthermore, the pool of candidates willing to put themselves forward for an independent race may differ from that of those comfortable campaigning on a joint ticket.…”
Section: About Those Separate Ballot Linesmentioning
confidence: 99%